Analisis Faktor - Faktor yang Mempengaruhi Struktur Modal Terhadap Nilai Perusahaan - santoso, Clairene elisha (Universitas Sam Ratulangi, 2019)
The purpose of this research aims to examine the factors that influence the capital structure (asset structure, company size, profitability, and risk) to the firm value. Analysis is carried out on 13 finance companies listed on the IDX using data from the 2013 financial reports to 2017. The result showed that assets structrure had no significant influence to capital structure, company size and bussines risk had positive significant influence to capital structure, whereas profitability had negative significant influence to capital structure. Asset structure, profitability and capital structure had no significant influence to firm value, whereas company size and bussines risk had significant influence to firm valueKeywords: Asset structure, company size, profitability, risk, capital structure, firm valueÂ